Título The quest for the evaluation of microfinance social performance - Sierra, Javier; Muriel-Patino, Victoria; Rodriguez-Lopez, Fernando (Iberoamerican Journal of Development Studies, 2020)
Several stakeholders have joined forces in recent years to facilitate consensus building on practices, indicators and standards that might serve to increase accountability and improve microfinance social performance. As a result, several sets of social standards have been developed to provide social performance assessment with a similar level of consistency and acceptance as those of financial performance. In this paper it is explored how standard-based evaluation methods may be used to test the underlying theory of change of microfinance, and the rate of use of existing methods in practice. Our findings suggest that social rating and social performance assessment using SPI4 are the most used methods. Nevertheless, standard-based methods are not suitable to assess the complete magnitude of microfinance social performance. Hence, microfinance social performance cannot rely on standard-based methods only, but need to use specific evaluation frameworks and indicators to fully measure microfinance effectiveness.